A formação de professores do Atendimento Educacional Especializado em um Centro de Formação e Acompanhamento à Inclusão no município de São Paulo - Miranda, Priscilla Mab Conti (2023)
This study aims to investigate how Teachers of Specialized Educational Assistance (PAEE), connected to a Regional Board of Education in the city of São Paulo-SP, understand their continuing education, considering the action of the Center for Training and Monitoring of Inclusion. As specific objectives were defined: to investigate the experiences of the active PAEE from 2016 to 2022 regarding continuing education, and to know their understandings about the training to work in the AEE and the training that they promote together with the educators of the school units they work with, addressing the challenges, needs or demands of the performance. For this, six teachers were interviewed and the concept of experience proposed by Vigotski (1934/2001) was used as the unit of analysis. The results point out that there is a search for complementing the formation for the performance in the AEE; continuing education was seen as necessary, as work demands boosted professional improvement in the area of Special Education. Regarding the training promoted by CEFAI, the reports addressed the relevance of learning and the exchange of experiences within the group, but also mentioned the need to expand the offer of courses to meet the specific demands of students eligible for the AEE. The formative action of the PAEE is seen as a link between the action of the AEE and its team and, from it, collaboration relationships and the construction of intervention strategies based on the specificities of the students arise. It was also highlighted that the work depends on the opening of the management team to be made possible and that the training actions bring contributions to all students, collaborating with a collective construction on inclusion. The experiences mentioned by the teachers emphasized moments of exchange of experiences that enabled the integration and socialization of the actions carried out, impacting and helping the reconfiguration of professional practice; actions developed by the teachers that denote the sense of appreciation of the professional activity and of belonging to a teaching group active in the inclusive perspective; as well as descriptions of significant brands, learning and signaling a change of perspective on the topics covered. It discusses the importance of making the work of the AEE collective and inclusive, considering the guidelines established by legislation, but, above all, meeting the training needs of teachers, in view of the challenges experienced in educational spaces.